A study on investor’s behavior towards investment avenues in Malaysia / Fatin Syafiqah Mohamad Ghazali and Masitah Salleh - Mohamad Ghazali, Fatin Syafiqah; Salleh, Masitah (Faculty of Business and Management, 2013)
Nowadays people start to realize the importance of stability of finance to ensure future life. One of the ways is by make an investment. But, from the study done by Howard (2013) stated that there are some investor make an investment based on emotional and not by rational. The main purpose of this study is to determine the factors that influence the investor behavior towards the investment avenues in Malaysia. This study was done to identify the most effective variables that will influence investor behavior such as investor’s effort, risk appetite and market psychology. Primary data was used in this using distribution of questionnaire. The aim is to get 150 respondents. From the distributed questionnaires, the data collected are analyzed using the Statistical Package for the Social Sciences (SPSS) 19.0. The Pearson Correlation was used to find the significant relationship between those variables. From the findings, all independent variables have significant result toward dependent variable and can be used in making evaluation for this study.